2007
DOI: 10.1016/j.jcrs.2007.06.046
|View full text |Cite
|
Sign up to set email alerts
|

Effect of antiglaucoma agents on postoperative intraocular pressure after cataract surgery with Viscoat

Abstract: Brinzolamide, brimonidine, acetazolamide, intracameral acetylcholine, and timolol had similar effects in reducing IOP increases after phacoemulsification performed using Viscoat.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
1
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 24 publications
1
25
1
2
Order By: Relevance
“…[20][21][22][23] In our study, the effectiveness of dorzolamide-timolol maleate combination was not different from that of oral acetazolamide.…”
Section: Discussioncontrasting
confidence: 43%
See 2 more Smart Citations
“…[20][21][22][23] In our study, the effectiveness of dorzolamide-timolol maleate combination was not different from that of oral acetazolamide.…”
Section: Discussioncontrasting
confidence: 43%
“…There was no statistically significant difference between two groups (p=0.924). The mean postoperative IOP (1 st day) of the first group was 15.27±2.90 (SD) (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23) mmHg and that of the second group was 14.82±2.57 (SD) (11-23) mmHg. There was no statistically significant difference between two groups (p=0.505).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…This can be avoided by administering oral acetazolamide or topical pressure-lowering agents in the immediate and early post-operative period. 24 Practice varies in different departments: a survey conducted in the UK showed that one-third of surgeons routinely used a pressure-lowering agent, and in most cases this was oral acetazolamide. 25 Some surgeons are more likely to use such agents in patients in whom IOP control is more critical, such as those with advanced glaucoma, as it has been suggested that glaucoma patients may be more likely to develop a rise in IOP.…”
Section: Raised Intraocular Pressurementioning
confidence: 99%
“…1,4 The problem with the vast majority of the studies that have investigated prophylaxis regimes for a raised IOP is that they have excluded patients suffering with glaucoma or OHT. [8][9][10][11][12][13][14][15][16][17][18][19] It is of importance to study such regimes specifically in glaucoma and OHT populations, as it is these patients who are most at risk of a raised IOP. 6,12,20 It has been suggested that this pressure rise may be transient postoperatively.…”
Section: Introductionmentioning
confidence: 99%